WAYS TO ORGANIZE LABOR AND IMPROVE ITS EFFICIENCY IN BUDGETARY ORGANIZATIONS (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article examines the current state of labor organization in budgetary organizations of Uzbekistan, identifies existing problems, and determines ways to improve efficiency. The study is based on the results of a structured survey and observation conducted in 2022–2023, involving 215 employees and 42 managers from 8 budgetary institutions in Bukhara region (education, healthcare, and culture sectors). Descriptive statistics and correlation analysis methods were applied. The results show that wage system imbalance (82%), limited opportunities for professional development (74%), and a low level of digital tool utilization (57%) are the main factors reducing labor productivity. In institutions that implemented reforms, the labor productivity index increased by 38% over 5 years, compared to only 7% in those that did not. The article concludes with specific mechanisms and recommendations for improving labor efficiency in budgetary organizations.
Keywords: budgetary organizations, labor efficiency, labor organization, motivation, wage system, professional development, digitalization, Uzbekistan.